Legal and ethical considerations in posting clinical images on social media - Shaikh, Zakirhusain (Research and Humanities in Medical Education, 2019)
It's becoming increasingly common to spot clinical images being shared on social media sites like Facebook and WhatsApp. Patients in operation theatres, newborns in incubators, women in labor ward and even cadavers in Dissection halls are photographed and shared. Many of these images reveal the identity of the patients and are posted for non-professional reasons without their consent. This is an illegal and unethical act which is liable for punishment and deregistration from medical council. Medical students and doctors need to be made aware of the legalities and ethics of posting clinical images on social media. Sensitization should start right from the dissection hall and need repeated reinforcements right through the internship. This calls for the role to be played by all concerned stakeholders including medical colleges, Medical Council of India, Indian Medical Association and social media sites. This would be a small step in restoring the crumbling doctor-patient relationship.